2013
DOI: 10.1089/ten.tea.2012.0453
|View full text |Cite
|
Sign up to set email alerts
|

Human iPSC-Derived Neural Crest Stem Cells Promote Tendon Repair in a Rat Patellar Tendon Window Defect Model

Abstract: Induced pluripotent stem cells (iPSCs) hold great potential for cell therapy and tissue engineering. Neural crest stem cells (NCSCs) are multipotent that are capable of differentiating into mesenchymal lineages. In this study, we investigated whether iPSC-derived NCSCs (iPSC-NCSCs) have potential for tendon repair. Human iPSCNCSCs were suspended in fibrin gel and transplanted into a rat patellar tendon window defect. At 4 weeks posttransplantation, macroscopical observation showed that the repair of iPSC-NCSC-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
81
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 89 publications
(83 citation statements)
references
References 54 publications
(63 reference statements)
2
81
0
Order By: Relevance
“…These types of hydrogel are particularly useful in examining cellular behaviour owing to their biocompatibility, biodegradability and biofunctionality [68]. cornea agarose-fibrin [29] alginate-gelatin nanofibre [163] collagen [146,149,150] collagen-PLGLA nanofibre [160] alginate [34] cellulose [35] heparin [36] alginate-hyaluronic acid [33] collagen [190] collagen-chitosan [32] dextran [30,31] hyaluronic acid [44] alginate [27] collagen [23,24] dextran [25] gelatin [26] collagen [17,97] fibrin [37] agarose [51,175,179,196] alginate [126] chitosan [20,50] fibrin [42,51] gellan gum [22,51] hyaluronic acid [110] PEG [60] A key factor when examining cell-material mechano-interactions is the mechanisms of cell adhesion to the hydrogel. Cell surface receptors such as integrins bind to ligands within the hydrogel if such adhesion sites exist.…”
Section: Cell-mediated Remodelling Of Hydrogelsmentioning
confidence: 99%
See 1 more Smart Citation
“…These types of hydrogel are particularly useful in examining cellular behaviour owing to their biocompatibility, biodegradability and biofunctionality [68]. cornea agarose-fibrin [29] alginate-gelatin nanofibre [163] collagen [146,149,150] collagen-PLGLA nanofibre [160] alginate [34] cellulose [35] heparin [36] alginate-hyaluronic acid [33] collagen [190] collagen-chitosan [32] dextran [30,31] hyaluronic acid [44] alginate [27] collagen [23,24] dextran [25] gelatin [26] collagen [17,97] fibrin [37] agarose [51,175,179,196] alginate [126] chitosan [20,50] fibrin [42,51] gellan gum [22,51] hyaluronic acid [110] PEG [60] A key factor when examining cell-material mechano-interactions is the mechanisms of cell adhesion to the hydrogel. Cell surface receptors such as integrins bind to ligands within the hydrogel if such adhesion sites exist.…”
Section: Cell-mediated Remodelling Of Hydrogelsmentioning
confidence: 99%
“…This remodelling behaviour is influenced by several factors, in particular, the type of hydrogel, the type of cell and the absence or presence of biochemical and mechanical stimuli. To date, cell-seeded hydrogels have been under investigation to repair or replace several tissue types, including cartilage [20][21][22], skin [23][24][25][26][27], cornea [28,29] and vascular tissues [30][31][32][33] among other tissues [34][35][36][37] (figure 1). As this field has grown, it has become evident that a greater understanding of the cell-material interactions in hydrogel systems is required to properly explain the mechanical mechanism that cells use to remodel their surroundings and to exploit this behaviour to develop functional tissues and tissue repair strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Induced pluripotent stem cells (iPSC) are especially promising cell sources for tissue engineering because iPSC reveal embryonic stem cell-like properties including high multi-differentiation and self-renewal capabilities [26,27]. PDLSC is originated from neural crest cells during development and our and other studies have demonstrated the successful generation of neural crest-like cells (NCLC) from iPSC [28][29][30][31][32][33]. Importantly, subcutaneously transplanted iPSC-derived NCLC revealed no capacity to form tumors.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Female Sprague-Dawley rats weighing 200-250 g were used in all experiments. We employed a well-established window defect model to create the injury in the rat patellar tendon as described previously [19]. Briefly, using the aseptic technique, animals under anesthesia were shaved off fur on both hind limbs, and the skin, soft tissue, and peritenon were dissected using a ventral longitudinal incision to expose the patellar tendon.…”
Section: Animals and Experimental Protocolmentioning
confidence: 99%